Information and Communication Technology Skills for Instruction Performance : Beliefs and Experiences from Public School Educators - Fatin Ardani, Zamri; Norhisham, Muhamad; Miftachul, Huda (Springer Cham, 2024)
This study was carried out to examine public educator’s beliefs and practices on managing Information and communication technology (ICT) skills in its usage in 21st century learning program. This study was conducted in seven secondary schools under Sarawak State Education Department Padawan District by distributing the questionnaire which has involved 69 respondents among the public educators in those schools. Retrieval results achieved were analyzed by using SPSS for Windows (version 23.0) software with descriptive method to obtain frequency, percentage, mean and standard deviation. An inference test such as Pearson Correlation was applied in this research in order to differentiate the relationship between variables. The final findings found that the level of public educator's skill through ICT usage in 21st century learning program is medium (min = 3.47, sd = 0.61). The research findings towards effectiveness through ICT application of 21st century learning program are quite high (min = 3.82, sp = 0.58). Despite that, the results also have proven that there is a high medium positive relationship between ICT usage skill with the effectiveness of teaching and learning process of 21st century learning program. Based on this study finding, it is hoped that public educators are able to enhance their skill in using latest and sophisticated applications together with students’ ability in the usage of gadgets to apply for 21st century learning program teaching and learning process.